2007
DOI: 10.1016/j.optmat.2005.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Concentration effect on the scintillation properties of sol–gel derived LuBO3 doped with Eu3+ and Tb3+

Abstract: Lu 1-x Eu x BO 3 and Lu 1-x Tb x BO 3 powders have been prepared by a sol-gel process with 0 < x < 0.15 for Eu 3+ and 0 < x < 0.05 for Tb 3+. The purity of powders has been verified by X-Ray diffraction and the results confirm that all the materials have the vaterite type even if the calcination has been performed at 800°C. Furthermore, the solid solution for LuBO 3 vaterite is observed up to x=0.15 and x=0.05 for europium and terbium ions respectively. So doping with Eu 3+ or Tb 3+ ions does not affect the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
40

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 9 publications
2
59
0
40
Order By: Relevance
“…The most intensive transition is 5 D 4 → 7 F 5 , which results in an overall green emission. The results are well agreement with the previous report about the sol-gel derived LuBO 3 :Eu 3+ /Tb 3+ (Sc-free materials) [34], beside the existence of a STE band in our materials. It is also observed that the 7 F 0 / 7 F 1 and 7 F 1 / 7 F 2 ratios of Eu 3+ -doped materials are changing upon X-ray excitation compared to PL spectra.…”
Section: Xrd Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…The most intensive transition is 5 D 4 → 7 F 5 , which results in an overall green emission. The results are well agreement with the previous report about the sol-gel derived LuBO 3 :Eu 3+ /Tb 3+ (Sc-free materials) [34], beside the existence of a STE band in our materials. It is also observed that the 7 F 0 / 7 F 1 and 7 F 1 / 7 F 2 ratios of Eu 3+ -doped materials are changing upon X-ray excitation compared to PL spectra.…”
Section: Xrd Characterizationsupporting
confidence: 93%
“…4b shows that the optimal Tb ions doping concentration is 0.3 at% and the corresponding light yield could reach a good value 23,800 ph/MeV. For sol-gel derived LuBO 3 :Eu 3+ /Tb 3+ (Sc-free materials) [34], the optimal scintillation light yield are obtained for Eu 3+ and Tb 3+ content of 5 at% in both cases, namely 8923 ph/MeV and 4398 ph/MeV. By comparison, the light yield of Tb doped LuBO 3 has significantly improved by doping Sc 3+ .…”
Section: Xrd Characterizationmentioning
confidence: 94%
“…ions and Tb 3? ions and has been used as one of the best hosts of red and green phosphors in the PDPs, the mercury-free fluorescence lamps and bioimaging materials [8][9][10][11]. Up to now, LnBO 3 micro/nanocrystals with abundant morphologies have been synthesized through a variety of techniques, such as hydro/solvothermal techniques, vapor-liquid-solid methods, co-precipitation, solgel routes and solution-combustion method [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…YBO 3 :Tb 3+ phosphor has been synthesized via various routes, such as solid-state reaction [7], sol-gel method [1,8], spray pyrolysis method [9] and hydrothermal method [10]. Compared to the other routes, the hydrothermal method is a promising synthetic route, which can be better controlled from the molecular precursor to the reaction parameters, such as the reaction time and temperature, to give highly pure and homogeneous materials.…”
Section: Introductionmentioning
confidence: 99%